KANDUNGAN NON NUTRISI DAN BILANGAN PEROKSIDA KERUPUK KULIT (KERUPUK JANGEK) - Nadia, Lula (LPPM Universitas Terbuka, 2006)
The aim of this research was to find the non nutrition compound of ‘kerupuk Jangek’. Several steps were used to determine: (1) the content of cholesterol, (2) the content of uric acid, (3) the content of peroxide, and (4) the hedonic value of  ‘kerupuk Jangek’ storaged for several period of time. The HPLC with ELSD detector analysis showed that no cholesterol was detected in both samples of the beef skin crackers and the buffalo skin crackers. Using Photometer 4020, it was found that there was 0.64 – 0.7 mg uric acid in 100 gr of the beef skin crackers. The rate of peroxide in the beef skin cracker was 1.0 mg/kg sample after 4 – 5 weeks storage in 30°C condition. From hedonic analysis, it was found that ‘kerupuk Jangek’ being rejected by the panelist after 7 weeks storage in 30°C condition, and the content of peroxide was 1.83 mg/kg. It is suggested that, the skin crackers should be consumed before 7 week storage in room temperature and it is not recommended for hyperuricemia one.